EFFICACY OF REMAXOL AND ADEMETHIONINE IN EXPERIMENTAL LIVER DAMAGE CAUSED BY A COMBINATION OF RESERVE-SERIES ANTITUBERCULOSIS DRUGS AND ALCOHOL - D. S. Sukhanov; E. B. Artyushkova; V. T. Dudka; S. V. Okovityi (Туберкулез и болезни лёгких)
The hepatic and endothelial protective effects of remaxol and S-adenosyl-L-methionine were studied on 24 male rats with liver damage caused by reserve-series antituberculosis drugs in combination with alcohol. The test agents were found to have a unilateral hepatoprotective effect in decreasing the blood levels of triglycerides, bilirubin, and alkaline phosphatase with a concurrent significant reduction in the manifestations of hyaline-drop and hydropic dystrophy of hepatocytes. Remaxol and ademethionine have the same endothelial protective activity manifested as normalization of an endothelium-dependent vasodilation response and endothelial dysfunction coefficient.